Telomere length is highly repeatable and shorter in individuals with more elaborate sexual ornamentation in a short‐lived passerine. Issue 23 (25th February 2022) - Kauzálová, Tereza; Tomášek, Oldřich; Mulder, Ellis; Verhulst, Simon; Albrecht, Tomáš
Abstract: Quantifying an individual's state as a fitness proxy has proven challenging, but accumulating evidence suggests that telomere length and attrition may indicate individual somatic state and success at self‐maintenance, respectively. Sexual ornamentation is also thought to signal phenotypic quality, but links between telomeres and sexual ornamentation have been little explored. To address this issue, we examined whether telomere length and dynamics are predicted by the expression of a sexually selected ornament, the length of the outermost tail feathers (streamers), using longitudinal data from a population of European barn swallows ( Hirundo rustica ). In 139 adult individuals, each measured twice, we further assessed associations of telomere length with age, sex, breeding status and survival. Telomere length showed high individual repeatability ( R  = .97) across years while shortening with age in both sexes. Telomere length and dynamics were not significantly associated with survival to the next year, remaining lifespan or reproduction status (comparing breeding and nonbreeding yearlings). Tail streamer length, a sexually selected trait in barn swallows, was negatively associated with telomere length, independent of sex. Thus, telomere length may reflect the costs of carrying an elaborated sexual ornament, although ornament size did not significantly predict telomere shortening. In conclusion, telomere length in adult barn swallows is a highly consistent trait that shows a negative relationship with sexual ornamentation, suggesting a trade‐off between sexual ornamentation and telomere length.